SLEEP MEDICINE IN ROMANIA - THE RESULTS OF A QUESTIONNAIRE APPLIED TO DOCTORS OF VARIOUS MEDICAL SPECIALTIES - Mihaela Oros; Florin Mihaltan (Amaltea Medical Publishing House, 2014)
Pediatric sleep medicine is an area of intense research. The importance of screening for obstructive sleep apnea syndrome (OSAS) has been emphasized in the recently published international guidelines for the diagnosis and management of childhood OSA. In Romania, the fi rst steps of diagnosis and treatment of sleep disorders in children have been recently made and we wanted to assess the current awareness and management option in a group of HCPs. A self-administered questionnaire was sent by email to pediatricians, family doctors, medical doctors of other specialties, including pneumologysts, psychiatrists and ENT specialists. The results, important for the qualitative information, show that pediatric sleep disorders, mainly OSAS, are diagnosed rather by specialists than by family doctors, and that in most cases the management strategy was re-evaluation of the child and/or referral to another specialist. Half of the respondents completed the fi nal open qestion showing the need for improvement, both theoretical and practical knowledge, for a better communication between specialists and improvement of access to diagnostic tools, as well as increase of education of parents and older children and adolescents. Further research is needed to confi rm these qualitative data, however the questionnaire allowed the identifi cation of poor areas for various working groups, fi nally elaborating recommendations for various interventions which might infl uence the development of this fi eld in our country as well.